2006
DOI: 10.1038/sj.onc.1209579
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of cyclooxygenase-2 by tumor suppressor p53 requires nuclear factor-kappaB

Abstract: Overexpression of cyclooxygenase-2 (Cox-2) is thought to exert antiapoptotic effects in cancer. Here we show that the tumor suppressor p53 upregulated Cox-2 in esophageal and colon cancer cell lines by inducing the binding of nuclear factor-kappaB (NF-kappaB) to its response element in the COX-2 promoter. Inhibition of NF-kappaB prevented p53 induction of Cox-2 expression. Cooperation between p53 and NF-kappaB was required for activation of COX-2 promoter in response to daunomycin, a DNAdamaging agent. Pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 50 publications
(51 reference statements)
4
44
0
1
Order By: Relevance
“…Thus, this p53-dependent SGK induction can be seen as compensatory mechanism, as previously reported for other p53-dependent genes coding for pro-survival candidates such as COX-2, for example [46,47]. This negative feedback loop may also explain why the Elongator deficient cells are not significantly more sensitive to the DNA-damaging-mediated apoptotic pathway.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, this p53-dependent SGK induction can be seen as compensatory mechanism, as previously reported for other p53-dependent genes coding for pro-survival candidates such as COX-2, for example [46,47]. This negative feedback loop may also explain why the Elongator deficient cells are not significantly more sensitive to the DNA-damaging-mediated apoptotic pathway.…”
Section: Discussionsupporting
confidence: 62%
“…Many findings have contributed to establishing the relationship between the expression of apoptosis and COX-2 (Benoit et al 2006;de Moraes et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on A549 cells have indicated that Akt and p38kinase pathways mediate apoptosis and inflammation (Jang 2009;Boo et al 2011). These pathways also play an important role in the regulation of many cellular responses, such as cell differentiation, proliferation, and cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, either dependent on the HB-EGF-induced activation of the ras/raf/MAPK pathway or in cooperation with NF-kB, p53 induces expression of the cyclooxygenase 2 (Cox-2) gene following exposure to various DNA-damaging agents. 44,147 Cox-2, a crucial enzyme in prostaglandin synthesis is often overexpressed in many solid tumors and associated with tumor aggressiveness due to its well documented anti-apoptotic and tumor-promoting capabilities. 148,149 Cox-2 was also demonstrated to regulate p53-induced apoptosis, as the rate of cell death following DNA damage was potentiated not only in Cox-2-deficient cells, but also in cells in which Cox-2 activity was suppressed by non-steroidal anti-inflammatory drugs such as NS-398 and celecoxib.…”
Section: P53 and Mitogen-activated Protein Kinasesmentioning
confidence: 99%